A context‐driven approach on coping with COVID‐19: From hiding knowledge toward citizen engagement. (19th March 2021) - Cegarra‐Navarro, Juan‐Gabriel; Vătămănescu, Elena‐Mădălina; Martínez‐Martínez, Aurora
Abstract : The current study sets out to investigate the relationships among three interconnected dimensions, that is hiding knowledge by the Government, the realized absorptive capacity (RACAP) and citizen engagement, giving way to a context‐driven approach. Emphasis is laid on the effects engendered by the lack of official information transparency in the critical context of COVID‐19 outbreak at the global level, through the lens of the Spanish example. The relationships among the variables are analyzed by means of an empirical study conducted with 151 Spanish subjects with a view to identify whether the impact of knowledge hiding by the Government on citizen engagement can be mitigated and to acknowledge how the presence of RACAP impacts citizens in limiting the spread of COVID‐19 information disorders.